Preventing type 2 diabetes mellitus in Qatar by reducing obesity, smoking, and physical inactivity: mathematical modeling analyses - Susanne F. Awad (11607966) (2019)
Background The aim of this study was to estimate the impact of reducing the prevalence of obesity, smoking, and physical inactivity, and introducing physical activity as an explicit intervention, on the burden of type 2 diabetes mellitus (T2DM), using Qatar as an example. Methods A population-level mathematical model was adapted and expanded. The model was stratified by sex, age group, risk factor status, T2DM status, and intervention status, and parameterized by nationally representative data. Modeled interventions were introduced in 2016, reached targeted level by 2031, and then maintained up to 2050. Diverse intervention scenarios were assessed and compared with a counter-factual no intervention baseline scenario. Results T2DM prevalence increased from 16.7% in 2016 to 24.0% in 2050 in the baseline scenario. By 2050, through halting the rise or reducing obesity prevalence by 10–50%, T2DM prevalence was reduced by 7.8–33.7%, incidence by 8.4–38.9%, and related deaths by 2.1–13.2%. For smoking, through halting the rise or reducing smoking prevalence by 10–50%, T2DM prevalence was reduced by 0.5–2.8%, incidence by 0.5–3.2%, and related deaths by 0.1–0.7%. For physical inactivity, through halting the rise or reducing physical inactivity prevalence by 10–50%, T2DM prevalence was reduced by 0.5–6.9%, incidence by 0.5–7.9%, and related deaths by 0.2–2.8%. Introduction of physical activity with varying intensity at 25% coverage reduced T2DM prevalence by 3.3–9.2%, incidence by 4.2–11.5%, and related deaths by 1.9–5.2%. Conclusions Major reductions in T2DM incidence could be accomplished by reducing obesity, while modest reductions could be accomplished by reducing smoking and physical inactivity, or by introducing physical activity as an intervention. Other Information Published in: Population Health Metrics License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1186/s12963-019-0200-1